Real world .NET, C♯, and Silverlight : indispensible experiences from 15 MVPs - Evjen, Bill (Programmer to programmer., 2012)
A team of MVP authors guides you through the .NET 4 Framework Written by a group of experienced MVPs, this unparalleled book delves into the intricate-and often daunting-world of .NET 4. Each author draws from a particular area of expertise to provide invaluable information on using the various .NET 4, C# 4, Silverlight 4, and Visual Studio tools in the real world. The authors break down the vast .NET 4 Framework into easily digestible portions to offer you a strong foundation on what makes .NET such a popular and successful framework for building a wide range of solutions.<di.